Wake up, beast - Vance, Debbie, author; Levy, EJ, advisor; Doenges, Judy, committee member; Little, Ann, committee member (Colorado State University. Libraries, 2018)
This thesis project takes the Pleaides/Orion myth as its origin. According to the myth, the great hunter Orion fell in love with the Pleiades, seven virginal sisters, and chased them around the world for seven years, until their mother, Pleione, interceded on their behalf to Zeus, at which point the girls were transformed into birds, then stars. Here, we meet a single mother, Nina Pleione, living in Gloucester, Massachusetts with her three daughters and a string of boyfriends. Though an act violence catalyzes this collection—Nina's boyfriend, Oren, sexually abuses her sixteen-year-old daughter, Mira—the stories primarily explore the relationships between girls and women, mothers, daughters, sisters, friends, asking what it means to come of age in America, among parents and siblings and friends who love, but not enough.